2010
DOI: 10.1021/jf904595q
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Dietary Melamine to Laying Ducks: Biochemical and Histopathological Changes and Residue in Eggs

Abstract: Jinding laying ducks (n = 648) were subjected to one of six dietary treatments (0, 1, 5, 25, 50, or 100 mg of melamine/kg of diet) to investigate the toxicity of melamine and determine the melamine residue in eggs. Ducks were fed melamine-supplemented diets for 21 days followed by a 21 day withdrawal period. Dietary melamine had no adverse effects on laying performance. Renal lesions were correlated with increasing levels of dietary melamine. Melamine residue in eggs increased with dietary melamine during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…None of the pigs displayed any abnormal clinical signs of melamine toxicosis during the experiment. The performance of pigs in this study demonstrated that there is no visible adverse effect from less than 1000 mg kg -1 dietary melamine, which is consistent with the previous studies on poultry, livestock and fishes Bai et al 2010;Gao et al 2010;Lv et al 2010).…”
Section: Growth Performancesupporting
confidence: 91%
“…None of the pigs displayed any abnormal clinical signs of melamine toxicosis during the experiment. The performance of pigs in this study demonstrated that there is no visible adverse effect from less than 1000 mg kg -1 dietary melamine, which is consistent with the previous studies on poultry, livestock and fishes Bai et al 2010;Gao et al 2010;Lv et al 2010).…”
Section: Growth Performancesupporting
confidence: 91%
“…The melamine concentration in the eggs fluctuated somewhat at around 21 d after first ingestion of the diets containing melamine at 10, 50, or 100 mg/kg. This result is consistent with previous reports that melamine concentration in eggs fluctuated continually around high levels until d 21 (Gao et al, 2010). Dong et al (2010) indicated that melamine concentration in eggs reached a maximum value at the 17th d after exposure, and values decreased somewhat over the next 4 d while hens were on the melamine treatment.…”
Section: Resultssupporting
confidence: 92%
“…This demonstrated that melamine is not metabolised into cyanuric acid in quails. Previous reports indicated that melamine concentration in eggs increased rapidly with exposure from feeds, and then reached a plateau within one week (Gao et al, 2010;Xue et al, 2010). For economic reasons and in line with the objective, melamine concentrations in the eggs were only reported from d 11 onwards.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Gao et al (2010) found in ducks that administration of higher doses of melamine in feed caused also histological lesions in the liver.…”
Section: Resultsmentioning
confidence: 99%